Sport promotion and sales management - Zahra Aminiroshan; Esmaiel Sharifian; Seyed Mostafa Siyadat (Management Science Letters)
At the beginning of third millennium, the world of sport has been experiencing new marketing techniques to introduce products and services. The purpose of this study was to compare advertising and sales promotion strategies, the effects of different strategies in sport production companies to retain or to gain market share among selected firms, which were active in Iran. The method of survey was descriptive – analytical and some questionnaires were used for collecting data in Likert scale. The validity of the questionnaire were estimated by interview with professors and exports in marketing and sport marketing and the reliability was assessed by using Cronbach's alpha (α= 0.89). Statistical population of the study includes Sport Goods-Producing companies in Iran (N= 180) and 122 firms formed the study sample. For testing the hypothesis, we have used Paired Samples T-Test. The analysis of findings showed that there was a meaningful difference between using advertising and sales promotion strategies. In general, we can say, there are some limited applications of using techniques and methods of sales promotion strategies in Iranian sport industry and methods of advertising. Consequently, regarding the intense competition among companies as well as fast growth of markets and fast changes in consumer’s behavior, identifying the best methods for corresponding relationship to customer would be required.